Exploring correlations between hyper-spectral signatures acquired in the laboratory and in-situ observation for heavy metal concentrations in soil - Lee, Keum Young; Kang, Seongjoo; Jeon, Eui-Ik; Yu, Sejong; Kwon, Ohseob (Spatial information research (Online), 2018)
This study is a preliminary study for monitoring of heavy metal pollution in soil using airborne hyperspectral sensor. This paper presents an approach to exploring the correlation between the spectrum of heavy metals in soil from hyperspectral imagery taken in the laboratory and its observed concentration. In order to identify spectral wavelengths with a high correlation coefficient, hyperspectral data were collected from soil containing various concentrations (10–5000 ppm) of As, Cd, Cu, and Pb. Correlation analysis was performed with the hyperspectral imagery between the spectrum and its observed concentration obtained from instrumental analysis. The selective spectral wavelengths with a correlation coefficient (R 2 ) above 0.80 will make a major contribution to study and monitoring of heavy metal pollution in soil using airborne hyperspectral sensor in the future. In order to accomplish desired result, further investigation is required.